Wafer-Level Testing and Test During Burn-In for Integrated Circuits. - Bahukudumbi, Sudarshan (Artech House, 2010)
Wafer-level testing refers to a critical process of subjecting integrated circuits and semiconductor devices to electrical testing while they are still in wafer form. Burn-in is a temperature/bias reliability stress test used in detecting and screening out potential early life device failures. This hands-on resource provides a comprehensive analysis of these methods, showing how wafer-level testing during burn-in (WLTBI) helps lower product cost in semiconductor manufacturing. Engineers learn how to implement the testing of integrated circuits at the wafer-level under various resource constrain.